An InSilico Study of Chirality of Benzimidazole Amine Hybrids on The Inhibition Effects on Human Carbonic Anhydrase Isoenzymes and Acetylcholine Esterases - ABDURRAHMANOĞLU, SUZAN (My University, 2022)
Benzimidazole-hybrid have a unique chemical structure which show tremendous pharmacological activity such as anti-inflammatory, antiviral, anti-histaminic, antimicrobial [1,2]. Due to their biological and therapeutic activity they have been studied extensively in recent years. For instance, Richards et.al. showed that the main benzimidazole structure has good efficacy in treating allergy and asthma [3]. Carbonic anhydrase (CA) regulates the acidity of the chemical environment in the body and prevents body functions from being damaged. Due to these vital physiological properties extensive studies have been performed on CA enzymes. Anti-acetylcholineesterases (anti-AChE) are used as anti-Alzheimer drugs to treat moderate Alzheimer disease because of their enhanced cognitive connectivity cholinergic neurotransmission in clinic applications. There are many CA and AChE inhibitiors identified and used in clinic treatments [4]. In this study, efficacy of novel chiral benzimidazole amine hybrids as CA and AChE inhibitors have been studied in silico and compared with the in vitro results. The binding energies (scoring based) were obtained as negative scores which proves that all compounds were successfully docked at the active sites of CA isoenzymes and AChE. The highest binding energies were observed in the case of AChE and these results are in consistent with the experimental data since all of the compounds have shown very good inhibition activity by means of IC50 values. The ADME (adsorption, distribution, metabolism and excretion) were also showed that these compounds could be recognised as drug like potential towards AChE and CA proteins